Care provision during termination of pregnancy following diagnosis of a severe congenital anomaly – A qualitative study of what is important to parents. (December 2016) - Lotto, Robyn; Armstrong, Natalie; Smith, Lucy K.
Abstract: Objective: to understand the experiences of women and their partners following the decision to terminate a pregnancy affected by a severe congenital anomaly Design: qualitative semi-structured interviews with a purposive sample of women and their partners who underwent a termination of pregnancy following diagnosis of a severe congenital anomaly. Setting: women referred to four fetal medicine centres across two hospital trusts. Analysis: data analysis was based on the constant comparative approach. Findings: the over-arching theme emerging from the data was that of 'falling through the gap', where the care received did not adequately meet the needs of women and their partners. This was particularly salient at three specific points in the care pathway: enacting the decision to have a termination of pregnancy and subsequent initiation of the process; care during labour and birth, where parents describe being caught in 'no-man's land' between the antenatal and postnatal settings; and post-birth, where parents made sense of and came to terms with their decision. Conclusions: the diagnosis of a severe congenital anomaly and the subsequent pathway that parents face is a traumatic event. Responsibility for the decision to terminate the pregnancy intensifies emotions and adds to the complexity of caring for this group. These findings point to the need for a specific care pathway for parents undergoing this difficult experience. Recommendations include the need for a greater understanding of the views of midwives caring for these parents, review of specific training needs, and examination of processes to better support both parents. Highlights: Provides an insight into the specific needs of parents who terminate a pregnancy affected by a severe congenital anomaly. Procedures often perceived as routine, such as signing a consent form, hold great symbolism to women and their partners. Parents felt a sense of being caught in 'no-man's land', of not belonging to either the antenatal or postnatal setting.